2009
DOI: 10.1080/87565640903133509
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Sleep Phenotype in Children With Autism

Abstract: Sleep concerns are common in children with autism spectrum disorders (ASD). We identified objective sleep measures that differentiated ASD children with and without parental sleep concerns, and related parental concerns and objective measures to aspects of daytime behavior. ASD poor sleepers differed from ASD good sleepers on actigraphic (sleep latency, sleep efficiency, fragmentation) and polysomnographic (sleep latency) measures, and were reported to have more inattention, hyperactivity, and restricted/repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 29 publications
14
157
0
5
Order By: Relevance
“…Mayes and Calhoun 23 reported that children with ASDs and sleep problems had more severe autistic symptoms, hyperactivity, mood variability, and aggression, than children with no sleep problems. Malow and colleagues [24][25][26] found associations among sleep problems and inattention, hyperactivity, ritualistic behavior, selfinjury, and affective problems. Because behavior symptoms and sleep habits in children with ASDs change with age, 27 it becomes important to look at the relationship between sleep problems and daytime functioning in children with ASDs at different ages.…”
mentioning
confidence: 99%
“…Mayes and Calhoun 23 reported that children with ASDs and sleep problems had more severe autistic symptoms, hyperactivity, mood variability, and aggression, than children with no sleep problems. Malow and colleagues [24][25][26] found associations among sleep problems and inattention, hyperactivity, ritualistic behavior, selfinjury, and affective problems. Because behavior symptoms and sleep habits in children with ASDs change with age, 27 it becomes important to look at the relationship between sleep problems and daytime functioning in children with ASDs at different ages.…”
mentioning
confidence: 99%
“…Сопротивление укладыванию. Опросник характеризуется удовлетворительными показателями внутреннего согласия, внутренней валидности и надежности [56], позволяя объектив-но оценить нарушения сна у детей [57]. Выявленные с его помощью нарушения сна подтверждаются объ-ективными методами диагностики, в частности ак-тиграфией [58].…”
Section: шкалы и вопросыunclassified
“…The CSHQ is a validated measure in the ASD population 29,30 and assesses various sleep problems. Questions are answered on a 3-point scale ("rarely," "sometimes," "usually"), and items rated as "sometimes" or "usually" were used to endorse sleep problems in the current study.…”
Section: Sleep Habits and Problemsmentioning
confidence: 99%